2013
DOI: 10.1038/ncomms2476
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind entry into the high-latitude terrestrial magnetosphere during geomagnetically quiet times

Abstract: An understanding of the transport of solar wind plasma into and throughout the terrestrial magnetosphere is crucial to space science and space weather. For non-active periods, there is little agreement on where and how plasma entry into the magnetosphere might occur. Moreover, behaviour in the high-latitude region behind the magnetospheric cusps, for example, the lobes, is poorly understood, partly because of lack of coverage by previous space missions. Here, using Cluster multi-spacecraft data, we report an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
134
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(151 citation statements)
references
References 45 publications
14
134
1
Order By: Relevance
“…Shi et al . [] found localized regions of high‐density ions in the lobe. The pitch angle distribution of the ions is almost isotropic, and the characteristic energy is ~ keV.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al . [] found localized regions of high‐density ions in the lobe. The pitch angle distribution of the ions is almost isotropic, and the characteristic energy is ~ keV.…”
Section: Discussionmentioning
confidence: 99%
“…One end of the magnetic field lines of the lobes connects to the solar wind downtail, and the other end connects to the polar cap of the ionosphere. The plasma density is very low, and the plasma is predominantly of ionospheric origin [e.g., Chappell et al , , ], though there is also some transfer of plasma from the solar wind across the magnetopause [e.g., Hultqvist et al , ; Shi et al , , and references therein]. Filling of lobe flux tubes starts with ionization of atoms and gas molecules in the thermosphere, accompanied by upflow due to thermal and electromagnetic forces.…”
Section: Introductionmentioning
confidence: 99%
“…Many people concentrate on the mechanism of the solar wind plasma entry into the magnetosphere during the IMF northward period, such as the high-latitude magnetic reconnection [3,4], impulsive penetration, the low latitudes instabilities or gradient drift. In this paper, we find that when the IMF is northward, although the formation of the entry layers depends on the direction of IMF, we pointed out that it mainly depends on the IMF Bx component and the influences of IMF By component could be weak.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There are many possible mechanisms such as high-latitude magnetic reconnection [3,4], impulsive penetration [5], the low latitudes instabilities [6] and gradient drift [7]. During the quiet times when the interplanetary magnetic field (IMF) is northward, using Cluster multi-spacecrafts observation data between August to October each year from 2002 to 2004, Shi et al (2013) reported some new regions of solar wind entry into the Earth's high-latitude magnetosphere tailward of the cusps where the solar wind plasmas penetrate into magnetosphere through the mechanism of high-latitude magnetic reconnection. In this paper, we used another period Cluster data which is between January to April each year from 2001 to 2006 to make further research on the transmission characteristics of the solar wind plasmas.…”
Section: Introductionmentioning
confidence: 99%